A Rising Foreign Labour Migration and Implications for Farming and Food Security in Nepal (Journal of Forest and Livelihood, 2024)
Escalating the import of food and diminishing domestic production signal a profound challenge for Nepal on its path to achieving food security. This challenge not only relates to the question of land and farming but also mirrors recent socio-economic changes mainly triggered by foreign labour migration. In this article, I examine foreign labour migration in relation to its effects on an agrarian economy, exploring socio-economic contours of food security shaped by land and labour relations. In doing so, this paper draws on fresh insights gained from case studies carried out in two villages representing the Tarai and hill geography of Nepal. These findings show that while foreign labour migration has benefited both migrant and non-migrant households through the inflow of remittances and creation of rural employment, commodification of land and subsequent dispossession have posed critical threats to food security of the poor as well as the nation. This article suggests that any discourses and policies that concern land, farming and food need to factor migration and the associated socio-economic processes and patterns of changes.